Coping with chronic complex regional pain syndrome: advice from patients for patients. (March 2013) - Rodham, Karen; McCabe, Candida; Pilkington, Melissa; Regan, Laurence
Objective: To explore what advice people currently living with chronic complex regional pain syndrome would offer to another person coming to terms with a diagnosis of chronic complex regional pain syndrome. Methods: Semi-structured interviews with 21 adults (5 male) living with chronic complex regional pain syndrome who had completed a complex regional pain syndrome rehabilitation programme were conducted. Results: Effectively self-managing complex regional pain syndrome required individuals to play an active role. This could only be achieved if they felt they had sufficient control. Means of attaining control involved attaining a level of acceptance, becoming well-informed and accessing the right kind of support. The advice offered by patients for patients largely reflected that offered by healthcare professionals. One area where there was a conflict concerned sleep hygiene. Conclusions: Our study provides support both for the argument put forward by Redman that without appropriate preparation and support, self-management is ineffective, and that by Skuladottir and Hallsdottir that the main challenge of the chronic pain trajectory is that of retaining a sense of control. The clinical implications of this are discussed.